Assessing single and multi-step friction stir consolidated recycled billets through uniaxial upsetting test - Latif, Abdul; Ingarao, Giuseppe; Fratini, Livan; Hetz, Peter; Merklein, Marion (Materials Research Proceedings, 2024)
Friction stir consolidation (FSC) represents a solid-state recycling technique that directly transforms machining waste into billets by the stirring action and friction heat of the rotating tool. This technology has demonstrated superior energy efficiency compared to remelting based traditional recycling methods. Concerning the FSC process mechanics, they impart temperature, strain and strain rate gradients across the billet sections leading to variations in mechanical properties such as hardness values and grain size distribution. Therefore, multi-step FSC variants were introduced to eliminate this inherent inhomogeneity inside the billets of the single-step FSC approach. However, the billets manufactured by multi-step methods showed better mechanical properties, and gradation across the billet section still persisted. This property led to the evolution of friction stir consolidation as a new manufacturing method for developing functionally graded materials. Previously, the gradation was highlighted by the Vickers hardness test and grain size distribution. Therefore, in the ongoing study, an advanced characterization technique was adopted by extracting miniaturized samples from the section of FSC billets and subjected them to the upsetting test. Employing advanced characterization techniques to get insights into the gradation and quality of billets manufactured through various process variants and will allow to draw a better conclusion regarding adoption of a more suitable FSC process variant.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Aluminum Alloys; Friction Stir Consolidation; Recycling; Upsetting Test

Characterization of an additively manufactured coating using an upsetting test with miniaturized cylindrical specimen - März, Raphaela; Hetz, Peter; Bartels, Dominic; Schmidt, Michael; Merklein, Marion (Proceedings of the Institution of Mechanical Engineers Part L-Journal of Materials-Design and Applications, 2024)
In order to reduce CO2 emissions in production industry, the combination of several manufacturing processes is coming to the fore. One example is the combination of metal additive manufacturing with the forming technology, whereby the advantages of both process technologies can be used. The process combination can be applied to produce hybrid barrel sleeves, for example. Using a laser-based directed energy deposition (DED-LB/M), a circular coating is first applied to a blank, which is then deep-drawn in a second step. The additive layer serves as a wear-resistant coating. One way to increase process understanding for this process combination is numerical simulation. An important part of setting up the simulation model is characterizing the material in terms of its mechanical behavior. In order to avoid long building times, small sample geometries are suitable for characterizing the additive material. In the context of the paper, the upsetting test is therefore carried out with miniaturized specimens, whereby not only the base material Bainidur AM but also the addition of tungsten carbide microparticles and carbon nanoparticles is investigated. The in-situ modification of the material significantly increases the yield strength, but at the same time reduces the ductility. The microhardness of the material is also increased by the addition of carbon or tungsten carbid
Keywords: DED-LB/M; hybrid parts; material characterization

Characterization of friction stir consolidated recycled billet by uniaxial compression tests with miniaturized cylindrical specimen - Latif, Abdul; Ingarao, Giuseppe; Fratini, Livan; Hetz, Peter; Merklein, Marion (Materials Research Proceedings, 2023)
Friction stir consolidation (FSC) is a solid-state recycling method that directly converts machining scraps into semifinished billets. This process has been proven to be a more energy efficient and environmentally friendly technique compared to remelting based conventional recycling methods. During FSC, machining chips are transformed into a solid billet by the stirring action and friction heat of the rotating tool. Due to process mechanics, especially temperature gradient and strain rate, billets have shown different hardness values and grain size distribution across their sections. Therefore, in this research, miniaturized upsetting samples are extracted from the FSC billet. The purpose of minimizing the sample size is to get the local properties of a particular position. The intensive characterization was performed with future goals to find a more accurate numerical modelling and ultimately assign FSC billet to a potential industrial application.
CRIS-Team Scopus Importer:2023-08-04
Keywords: Aluminum Alloys; Compression Test; Friction Stir Consolidation; Recycling

Characterization of sheet metal components by using an upsetting test with miniaturized cylindrical specimen - Hetz, Peter; Kraus, Martin; Merklein, Marion (CIRP Annals - Manufacturing Technology, 2022)
Especially for safety-relevant components local characterization of the mechanical properties is necessary for product testing. For sheet metal parts with a complicated geometry conventional specimens for standardized tests cannot be extracted due to size limitations. Thus, a novel extraction procedure of miniaturized upsetting specimens is investigated. Taking a miniaturized upsetting specimen out of the sheet component allows for the first time the characterization of sheet metals in a standardized upsetting test under uniaxial compression stresses. Furthermore, this enables the analysis of strain hardening behavior of components and a direct validation of finite element simulations based on the true stress.
CRIS-Team Scopus Importer:2022-08-12
Keywords: Material characterization; Metal forming; Wire EDM

Characterization of temperature-dependent tension-compression asymmetry for high-strength aluminium alloys - Hetz, Peter; Merklein, Marion (Production at the leading edge of technology. Proceedings of the 9th Congress of the German Academic Association for Production Technology (WGP), 2019)
In the course of lightweight construction, modern materials with high strength and low density are essential. High-strength aluminium alloys such as 7000 series aluminium alloys meet these requirements but are only limited formable at room temperature. Thus, different heat assisted sheet metal forming processes are used to increase the formability. First investigations on the highstrength aluminium alloy AA7075 show a temperature-dependent and tensilecompressive asymmetric material behaviour. Since both tensile and compressive forces occur in sheet metal forming processes, an understanding of temperaturedependent tension-compression asymmetry is vital to set up material models for process design. Until now, the tension-compression asymmetry has barely been investigated for high-strength aluminium alloys at different temperatures. Therefore, further experimental studies are necessary. Within this contribution, the material behaviour of AA7020-T6 and AA7075-T6 is hence examined under uniaxial tensile and compressive load at different temperatures. For this purpose, both tensile and compressive tests are carried out on flat specimens between room temperature and 200 °C.<br
Keywords: Tension-compression asymmetry; High-strength aluminium alloy; Warm forming

Contact pressure-dependent friction compensation in upsetting tests with miniaturized specimens - Hetz, Peter; Rentz, Marcel; Merklein, Marion (Materials Research Proceedings, 2023)
Components produced by sheet metal forming can so far only be characterized locally to a limited extent using conventional tests, such as the tensile test or the hydraulic cupping test, due to the size of the specimen. A new approach based on miniaturized upsetting specimens taken from the sheet plane allows to determine the material properties of semi-finished products locally, for example in radii. However, in addition to this specific advantage, challenges such as friction between the specimen and the tool also appear with this testing method. For an accurate determination of the material parameters, it is therefore necessary to correct the test force by the friction coefficient. According to the state of the art, a variety of tests for friction coefficient characterization exist. By using a novel numerical method, friction coefficients for upsetting tests can be calculated contact pressure-dependent by means of an experimental single layer upsetting test. Therefore, in this paper, this method will be used for the first time to compensate the friction part in an upsetting test with miniaturized specimens as a function the contact pressure. This can improve the experimental mapping of the material behavior in the uniaxial compression stress state with increasing strain and hardening, since share of friction force increases with a higher deformation in the upsetting test. In contrast, a friction coefficient compensation based on an average value is provided in order to analyze, whether or in which case a contact pressure-dependent friction compensation is appropriate. In particular, for upsetting tests with miniaturized specimens, these results are relevant, since a major advantage of this test compared to conventional tests besides the local component characterization is the determination of material properties at high strains.
CRIS-Team Scopus Importer:2023-04-28
Keywords: Friction; Metal Forming; Upsetting Test

Determination of the biaxial anisotropy coefficient using a single layer sheet metal compression test - Hetz, Peter; Lenzen, Matthias; Kraus, Martin; Merklein, Marion (19th International Conference on Sheet Metal, SheMet 2021, 2021)
Keywords: Anisotropy; Metal forming; Material characterization

Failure behavior of different sheet metals after passing a drawbead - Schmid, Harald; Hetz, Peter; Merklein, Marion (47th SME North American Manufacturing Research Conference, NAMRC 47, Pennsylvania, USA, 2019)
LFT Import::2019-08-05 (2364)

Investigation of the Influence by Size Effects on the Material Characterization of the Uniaxial Compression Stress State - Hetz, Peter; Kraus, Martin; Merklein, Marion (Key Engineering Materials, 2022)
For the evaluation of final component properties under consideration of production-induced material characteristics, it is necessary to determine the mechanical parameters of parts and structures. Thus, there is a need of new test methods for the material characterization and quality control of produced goods. The miniaturization of the test specimens offers the potential for the local testing of the material properties at almost any position on the component. However, due to the reduction in size of the test specimens, size effects can occur which may affect the material behavior. For this reason, this contribution analyses the influence of size effects on the derived material parameters in dependence of the specimen size and material by using upsetting tests according to DIN 50106:2016 standard. The materials Cu-OFE (copper), X5CrNi18-10 (stainless steel) and AA7075-T6 (aluminum) are investigated to ensure a broad transferability of the findings. The specimens are cut from a bar stock by using a high precision 3D micro electrical discharge milling machining. Due to the small size, every specimen is measured with an optical 3D coordinate measuring system to determine the exact size. Through these investigations, the reproducibility and scatter in the determination of material properties for scaled cylindrical upsetting specimens are evaluated. Furthermore, limits of geometric dimensions at constant aspect ratios are derived. The results of this investigation enable an estimation of the geometrical influence of the specimen size in regard to the mechanical properties.
CRIS-Team Scopus Importer:2022-11-04
Keywords: Compression test; Material characterization; Miniaturization; Size effects

Investigation of the Springback Behaviour of High-strength Aluminium Alloys Based on Cross Profile Deep Drawing Tests - Hetz, Peter; Suttner, Sebastian; Merklein, Marion (Procedia Manufacturing, 2020)
The prediction of springback of sheet metal parts is still a challenge in metal forming processes. To meet the requirements for dimensional accuracy of a sheet metal part, the springback must be compensated and the production process has to be designed accordingly. During forming, elastic energy is stored in the semi-finished product. When removing a part from the deep-drawing tool, the resulting residual stresses with an elastic component cause unwanted changes of the part`s geometry in forming. Especially sheet materials with low elastic modulus and high yield strength tend to an increased springback. Among others, these materials include aluminium alloys of the 7000 series. For this reason, a fundamental understanding of the material behaviour of these materials is relevant for designing a sheet metal forming process. This contribution uses a novel approach to investigate the springback behaviour of AA7020-T6 and AA7075-T6. For this purpose, cross profiles are deep-drawn with various parameter settings and subsequently digitised with a three-dimensional optical measurement system. By analysing the digitised profiles, the springback behaviour is quantified depending on the experimental parameters. Due to the right-angled structure of the cross profile, the influence of anisotropy in 0 and 90 degree to rolling direction is investigated within one forming operation.
CRIS-Team Scopus Importer:2020-06-05
Keywords: Cross profile; Deep drawing; High-strength aluminium alloys; Springback compensation

Numerical springback prediction for high-strength aluminum alloys based on the sheet metal upsetting test - Hetz, Peter; Merklein, Marion (Proceedings of the Institution of Mechanical Engineers, Part B: Journal of Engineering Manufacture, 2024)
Springback prediction continues to play a special role in the process design of sheet metal forming processes. During the forming process, elastic energy is stored in the sheet metal, which is released after the tool is opened. The dimensional accuracy and the function of the component in particular can be negatively affected by this. For this reason, the springback is predicted by means of numerical modeling in order to improve the process design. The simulation accuracy depends primarily on the used material model to map the stress-dependent material behavior and the quality of the experimental input data. High-strength aluminum alloys, which have a distinctive springback behavior, have a slightly pronounced tensile-compressive asymmetry. Since tensile and compressive stresses often occur in sheet metal forming processes, the consideration of this effect can lead to an improvement in springback prediction. Besides modeling the yield locus curve for describing the yield strength in the plane stress area, the yield curve data is also relevant for determining the strain hardening behavior. The work hardening is usually characterized by the tensile test or the hydraulic bulge test, which is used to describe the material behavior in the tensile stress state. A promising experimental method for the analysis of the material in the uniaxial compressive stress state is the sheet metal upsetting test. In addition to a local characterization of sheet metal materials, this test also enables the investigation of the material behavior at significantly higher plastic strains than in the tensile test. Thus, in this contribution it is examined to what extent the sheet metal upsetting test is suitable for improving the springback prediction quality of material models in sheet metal forming processes.
CRIS-Team Scopus Importer:2024-11-01
Keywords: high-strength aluminum alloys; material characterization; Springback; upsetting test